EMPLOYEE WORK ABILITY IN THE CONTEXT OF HEALTH SERVICE QUALITY IMPLEMENTATION - Fatmah. M. Ngabito (LP2M Universitas Bina Mandiri Gorontalo, 2022)
Research on Employee Work Ability in the Context of Health Service Quality Implementation The method used in this research is to use a quantitative research approach that aims to measure how much influence the independent variable has in this case the employee's work ability on the dependent variable in this case the implementation of health service quality at Ponelo Health Center North Gorontalo Regency Islands. With the number of populations at the Ponelo Islands Health Center, North Gorontalo Regency less than 100, the sampling technique used was saturated sampling (census) in which all members of the population were sampled, totaling 28 people. With Validity Test. With the results of the study that the variable of employee work ability (X) on the implementation of the quality of health services (Y) of employees at the Ponelo Islands Health Center, North Gorontalo Regency. The Fcount value is 8.912 while the Ftable value is 4.23. So that there is an effect of employee work ability (X) on the implementation of health service quality (Y).